2012
DOI: 10.1093/schbul/sbs001
|View full text |Cite
|
Sign up to set email alerts
|

The Cognitive Assessment Interview (CAI): Reliability and Validity of a Brief Interview-Based Measure of Cognition

Abstract: Objective: To obtain Food and Drug Administration approval for the treatment of cognitive impairments associated with schizophrenia, a drug will need to demonstrate benefits beyond those that may be documented on objective cognitive tests. Interview-based measures of cognition such as the Cognitive Assessment Interview (CAI) are candidate coprimary outcome measures. Methods: Psychiatrically stable schizophrenia outpatients (n 5 150) were studied using the CAI to obtain information about cognitive functioning f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 35 publications
1
36
0
Order By: Relevance
“…Previous reports suggested variable correlations between interview-based assessments and cognitive performance measures, ranging from −0.40 (Keefe et al, 2006) in a single site study to −0.31 in the 5-site MATRICS validation study (Green et al, 2008) with the SCoRS and −0.40 (Ventura et al, 2013) in a single site study to −0.23 in the 4-site MATRICS Validation of Intermediate Measures study (Green et al, 2011) with the CAI. The current data collected in a three-site research center consortium suggest that overall MCCB composite scores and SCoRS total ratings can have high correlations (r=0.46) when interviewers are highly trained and have access to reliable informants.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports suggested variable correlations between interview-based assessments and cognitive performance measures, ranging from −0.40 (Keefe et al, 2006) in a single site study to −0.31 in the 5-site MATRICS validation study (Green et al, 2008) with the SCoRS and −0.40 (Ventura et al, 2013) in a single site study to −0.23 in the 4-site MATRICS Validation of Intermediate Measures study (Green et al, 2011) with the CAI. The current data collected in a three-site research center consortium suggest that overall MCCB composite scores and SCoRS total ratings can have high correlations (r=0.46) when interviewers are highly trained and have access to reliable informants.…”
Section: Discussionmentioning
confidence: 99%
“…For this study, we did not include the social cognition measure from the MCCB, the Mayer-Salovey-Caruso Emotional Intelligence Test (MSCEIT) because several recent meta-analyses (e.g., Fett et al, 2011; Ventura et al, 2013) found that social cognition measures are minimally correlated with neurocognitive test performance and that neurocognition and social cognition are associated with different outcomes. We calculated a composite score, an average of the 9 age-corrected T-scores based on the neurocognitive tests in the MCCB, using the MCCB normative program, as our critical dependent variable.…”
Section: Methodsmentioning
confidence: 99%
“…We had patients and the high contact clinicians complete the Cognitive Assessment Inventory (CAI; Ventura et al, 2013). This is a 10-item instrument that asks the person making the judgments about cognition to rate severity of impairments in a variety of cognitive domains.…”
Section: Methodsmentioning
confidence: 99%
“…These research participants also provided self-reports regarding their current mood, and everyday functioning in three different functional domains with a previously validated rating scale (Schneier & Streuening, 1983). They completed a structured self-report assessment of cognitive performance (Ventura et al, 2013) and were examined with a metacognitive variant of the Wisconsin Card Sorting Test (Koren et al, 2004; 2005). High contact clinicians also generated identical functioning and cognitive performance ratings, while unaware of the patients’ performance on the assessment measures and their self-reports.…”
Section: Introductionmentioning
confidence: 99%